Improvement Physical Fitness Level on Mountain Climbing Athletes: High-Intensity Interval Training and Oregon Circuit Training Effect - Festiawan, Rifqi; Lim Boon Hooi; Kartono Pramdhan; Masnur Ali; Arief Nuryadin (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of this study was to compare the impact of giving High Intensity Interval Training (HIIT) and Oregon Circuit Training on cardiorespiratory endurance abilities. This study used an experimental method with a two group pretest-posttest design. The study population consisted of 20 people, the sample was determined by the total sampling method so that a sample of 20 people was obtained, the sample was then divided into two groups, the HIIT group (10 people) and the Oregon Circuit Training (10 people). The instrument used was the Multistage Fitness Test (MFT). Data analysis using Paired T-Test and Independent T-Test. The results showed that there was an effect of High Intensity Interval Training (HIIT) on the increase in VO2 Max (ρ value = 0.001), there was an effect of Oregon Circuit Training on the increase in VO2 Max (ρ value = 0.002) and, there was no significant effect comparison between High Intensity. Interval Training (HIIT) and Oregon Circuit Training (ρ value = 0.759), the conclusion is that the increase in cardiorespiratory endurance ability is influenced by the provision of both types of exercise but there is no significant comparison of the effects between the two, as well as the High Intensity Interval Training (HIIT) training method. ) showed more effective results (39, 69%). From these results, the HIIT training method or Oregon Circuit Training can be an alternative exercise to increase VO2 Max and can be used for further research with different variables.